Peasant perception of beekeeping constraints and practices in large honey production areas in Burkina Faso - Oswald Gilbert Dingtoumda; Marcellin Yamkoulga; Souhaïbou Sawadogo; Koï Wenceslas Kam; Zakaria Ilboudo (BMC, 2024)
Abstract Background In recent decades, agricultural landscapes have been profoundly modified due to the intensification of agriculture, therefore leading to significant disturbances in all components of biodiversity. A survey on the knowledge of beekeeping realities and the use of phytosanitary products in areas of high honey production in Burkina Faso was carried out. Beekeeping realities design the state of beekeeping activities in the study localities. Methods The objective of this survey was to characterize Beekeeping operations and to assess the level of knowledge of beekeepers on the effects of the use of phytosanitary products through different beekeeping and agricultural practices. In this sense, 113 farmer beekeepers from the Boucle du Mouhoun, Hauts-Bassins and Nord regions in Burkina Faso were surveyed about their different beekeeping practices. Results The results obtained indicated that beekeeping is a secondary activity (96.47%) and is mainly practiced by men (90.27%). The respondents have mostly an average of 22 traditional hives. The majority of beekeepers have not received training (84.07%) on the hazards of plant protection products on their beekeeping farms. However, a large amount of beekeepers (70.73%) acknowledged that the use of plant protection products could be harmful to their activity. Hives are usually installed in or near the fields. The plant protection products used for crop protection are herbicides (27%), insecticides (23%), fungicides (8%), but especially mixed (42%). Conclusion The results show that beekeeping in Burkina Faso remains traditional and is practiced for sociocultural reasons. The use of pesticides close to beekeeping could play a role in bee colony collapse taking place in these regions. Training beekeepers on the dangers of the chemicals they use in fields near hives is therefore essential.